PENGARUH KINERJA KEUANGAN PERUSAHAAN TERHADAP RETURN SAHAM - Ridho Al Chivalry (MNJ 16 UMY 135, 2016)
This study was conductedtoanalyze theInfluence ofCorporate Financial PerformanceReturnSharesAgainstManufacturing CompanyinIndonesia Stock Exchange. Sampling technique usedispurposivesamplingwithcriteria ofmanufacturing companies inthe Indonesia Stock Exchangeservingthe completefinancial statements ofthe period2010-2013. Obtaineda total sample of74 companiesout of129manufacturing companiesin Indonesia Stock Exchange2010-2013period. Based on the results of multiple regression test obtained by the findings that the independent variables that significantly affect stock return is solvency (ROE), profitability (ROE), investment as opportunity set (MBVE), liquidity (CR) had no significant effect on stock returns, and together - each (simultaneously) the liquidity, solvency, profitability, investment opportunity set to return stock. Keywords: liquidity (CR), solvency (DER), profitability (ROE), investment opportunity set (MBVE) on stock returns and multiple regression.